Mixed nonlinear localization strategy for the buckling and post-buckling analyses of structures: parameter optimization and path following implementation. Issue 2 (1st February 2017) - Hinojosa, J.; Allix, O.; Guidault, P. A.; Cresta, Ph.; Saavedra, K.
ABSTRACT: In previous work, the nonlinear localization was first presented and studied in the case of large displacements but only for globally stable structural responses. In this paper, the influence of the local error criterion on the performance of the strategy is investigated in structures exhibiting more complex behaviour, such as snap-through and snap-back. Second, a path following method is implemented in the domain decomposition framework of the strategy in order to track the solution around a critical point (snap-through and snap-back).